2007
DOI: 10.3758/bf03193500
|View full text |Cite
|
Sign up to set email alerts
|

Memory for scenes: Refixations reflect retrieval

Abstract: Most conceptions of episodic memory hold that reinstatement of encoding operations is essential for retrieval success, but the specific mechanisms of retrieval reinstatement are not well understood. In three experiments, we used saccadic eye movements as a window for examining reinstatement in scene recognition. In Experiment 1, participants viewed complex scenes, while number of study fixations was controlled by using a gaze-contingent paradigm. In Experiment 2, effects of stimulus saliency were minimized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 61 publications
(87 reference statements)
12
32
0
1
Order By: Relevance
“…Consistent with previous findings of gaze reinstatement (Bone et al, 2018;Foulsham & Kingstone, 2013;Holm & Mäntylä, 2007;Johansson & Johansson, 2013;Kumcu & Thompson, 2018;Laeng et al, 2014;Scholz et al, 2016; for review, see Wynn, Shen, et al, 2019), retrievalrelated EMs were more similar to the EMs enacted during encoding of the same (old) or similar (lure) image than to the EMs enacted during encoding of other images, suggesting that they reflect image-specific memory. In line with our predictions, gaze reinstatement was significantly greater than chance at all levels of test probe degradation, indicating that given an incomplete cue, EMs facilitate reactivation of a specific item representation from memory.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with previous findings of gaze reinstatement (Bone et al, 2018;Foulsham & Kingstone, 2013;Holm & Mäntylä, 2007;Johansson & Johansson, 2013;Kumcu & Thompson, 2018;Laeng et al, 2014;Scholz et al, 2016; for review, see Wynn, Shen, et al, 2019), retrievalrelated EMs were more similar to the EMs enacted during encoding of the same (old) or similar (lure) image than to the EMs enacted during encoding of other images, suggesting that they reflect image-specific memory. In line with our predictions, gaze reinstatement was significantly greater than chance at all levels of test probe degradation, indicating that given an incomplete cue, EMs facilitate reactivation of a specific item representation from memory.…”
Section: Discussionsupporting
confidence: 86%
“…For example, whereas fixed viewing impairs memory (Armson, Ryan, & Levine, 2019;Bochynska & Laeng, 2015;Henderson, Williams, & Falk, 2005;Johansson, Holsanova, Dewhurst, & Holmqvist, 2012;Johansson & Johansson, 2013), spontaneous gaze shifts to regions corresponding with previously encoded (i.e., viewed) image features has been shown to facilitate reactivation of those features and the relations among them (Noton & Stark, 1971a, 1971b; for review, see Wynn, Shen, et al, 2019). Reinstatement of encoding-related EMs, or gaze reinstatement, during memory maintenance (Olsen, Chiew, Buchsbaum, & Ryan, 2014;Wynn, Olsen, Binns, Buchsbaum, & Ryan, 2018) and retrieval (Damiano & Walther, 2019;Holm & Mäntylä, 2007;Laeng & Teodorescu, 2002;Wynn et al, 2016) has been associated with mnemonic performance across a variety of tasks. Even in the absence of visual input, humans spontaneously direct their gaze to image regions previously inspected during encoding (i.e., "looking at nothing"), and this gaze reinstatement has been correlated with explicit measures of memory.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed later, this unexpected finding could reflect ERS in eye movement patterns (Holm & Mäntylä, 2007; Laeng & Teodorescu, 2002). …”
Section: Resultsmentioning
confidence: 69%
“…One possible explanation is that item-ERS in this region reflects ERS in eye movements and that this similarity enhanced memory. Consistent with this idea, eye movement studies have shown ERS in eye movement patterns is associated with better memory (Holm & Mäntylä, 2007) and that participants reinstate encoding eye movements during retrieval, even during free recall (Laeng & Teodorescu, 2002). If confirmed, this effect would add to growing evidence for the role of eye movements in visual memory (for a review, see Hannula et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
“…The prediction of an association between mental imagery content and concurrent oculomotor movements is by no means a novel one, and it has received empirical support dating back several decades (Brandt and Stark, 1997; Spivey and Geng, 2001; Laeng and Teodorescu, 2002; Johansson et al, 2006; Holm and Mäntylä, 2007; Ryan et al, 2007; Hannula and Ranganath, 2009; Williams and Woodman, 2010; Johansson and Johansson, 2014; Martarelli et al, 2016). In a direct comparison between visual inspection and mental visualization, repetitive sequences of fixation across diagrammatic checkerboard stimuli were recorded and analyzed in relation to the scanpaths observed during mental imagery of the same stimuli (Brandt and Stark, 1997).…”
Section: Exploration and Evaluation Of Methodsmentioning
confidence: 99%